Thrombin-mediated activation of factor XI results in a thrombin-activatable fibrinolysis inhibitor-dependent inhibition of fibrinolysis. - Von dem Borne, P A; Bajzar, L; Meijers, J C; Nesheim, M E; Bouma, B N (The Journal of Clinical Investigation, 1997)
Recently, it has been shown that Factor XI can be activated by thrombin, and that Factor XIa significantly contributes to the generation of thrombin via the intrinsic pathway after the clot has been formed. This additional thrombin, generated inside the clot, was found to protect the clot from fibrinolysis. A plausible mechanism for this inhibitory effect of thrombin involves TAFI (thrombin-activatable fibrinolysis inhibitor, procarboxypeptidase B) which, upon activation, may inhibit fibrinolysis by removing carboxy-terminal lysines from fibrin. We studied the role of Factor XI and TAFI in fibrinolysis using a clot lysis assay. The lysis time was decreased twofold when TAFI was absent, when TAFI activation was inhibited by anti-TAFI antibodies, or when activated TAFI was inhibited by the competitive inhibitor (2-guanidinoethylmercapto)succinic acid. Inhibition of either TAFI activation or Factor XIa exhibited equivalent profibrinolytic effects. In the absence of TAFI, no additional effect of anti-Factor XI was observed on the rate of clot lysis. We conclude that the mechanism of Factor XI-dependent inhibition of fibrinolysis is through the generation of thrombin via the intrinsic pathway, and is dependent upon TAFI. This pathway may play a role in determining the fate of in vivo formed clots.